Assessment of reliability and validity of the Malay version PedsQL 3.0 cardiac module - Zain, Farohah Che Mat (2016)
OBJECTIVE To produce a reliable and validated Malay version of the PedsQLTM 3.0 Cardiac Module. METHODS This is a cross sectional study involving children with congenital heart disease between 5-17 years old and parent of children with congenital heart disease aged 2- 18 years old. A total of 528 participants were enrolled into this study when they presented to the pediatric cardiology clinic and echocardiography clinic at Hospital Raja Perempuan Zainab II and Hospital Universiti Sains Malaysia. The methods used including forward and backward translation, face and content validation of Malay version of the PedsQLTM 3.0 Cardiac Module questionnaires. RESULT Most of 27 items in PedsQLTM 3.0 Cardiac Module questionnaires showed satisfactory internal consistency with Cronbach Alpha exceeding 0.7 and good correlation with intraclass correlation coefficient 0.76-0.98. There were no missing data. CONCLUSION The result generally supports reliability and validity of Malay version PedsQLTM 3.0 Cardiac Module in assessing HRQOL among children with heart disease.